80+6a=7a-145

Simple and best practice solution for 80+6a=7a-145 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 80+6a=7a-145 equation:


Simplifying
80 + 6a = 7a + -145

Reorder the terms:
80 + 6a = -145 + 7a

Solving
80 + 6a = -145 + 7a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-7a' to each side of the equation.
80 + 6a + -7a = -145 + 7a + -7a

Combine like terms: 6a + -7a = -1a
80 + -1a = -145 + 7a + -7a

Combine like terms: 7a + -7a = 0
80 + -1a = -145 + 0
80 + -1a = -145

Add '-80' to each side of the equation.
80 + -80 + -1a = -145 + -80

Combine like terms: 80 + -80 = 0
0 + -1a = -145 + -80
-1a = -145 + -80

Combine like terms: -145 + -80 = -225
-1a = -225

Divide each side by '-1'.
a = 225

Simplifying
a = 225

See similar equations:

| X+47=183 | | 180.75=40+5*x | | (2x-1)*6=(4-x)*3 | | 157=x-987 | | -5(3x+5)-3=-5(x+3)+2x | | 7((16)-1/2) | | x+2(x+1)=24+(x+4) | | 4x+3x+2=9 | | 15x-6=40x+9 | | 1/2n+2.5=18 | | 2x^2-51=0 | | (25x^2-10x-3)=0 | | 6.16=x-7z | | -5u+u+4u+6= | | x+2(x+1)=68-3(x+2) | | 2.3x+1.2+2.5x=9.2-4.3 | | 2/5e-15=10 | | -4b=30 | | 9g-6=12g+1 | | 5x^2=12x-3 | | (20x^2-11x-4)=0 | | -4=30 | | -3t-8+7t=34 | | (5x^2+7x)=0 | | -22=x+6 | | 4x+y+4=0 | | (4x^2-2x)x-1=0 | | 5+9i/2+6i | | 5a-2b-8a+5+2b= | | 6x+7y-42=0 | | 7x+7=133/10 | | 50-3x=7x-80 |

Equations solver categories